Allosterically Linked Binding Sites in Serotonin Transporter Revealed by Single Molecule Force Spectroscopy - Zhu, Rong (Front Mol Biosci, 2020)
Crystal structures and experiments relying on the tools of molecular pharmacology reported conflicting results on ligand binding sites in neurotransmitter/sodium symporters (NSS). We explored the number and functionality of ligand binding sites of NSS in a physiological setting by designing novel tools for atomic force microscopy (AFM). These allow for directly measuring the interaction forces between the serotonin transporter (SERT) and the antidepressant S-citalopram (S-CIT) on the single molecule level: the AFM cantilever tips were functionalized with S-CIT via a flexible polyethylene glycol (PEG) linker. The tip chemistry was validated by specific force measurements and recognition imaging on CHO cells. Two distinct populations of characteristic binding strengths of S-CIT binding to SERT were revealed in Na(+)-containing buffer. In contrast, in Li(+)-containing buffer, SERT showed only low force interactions. Conversely, the vestibular mutant SERT-G402H merely displayed the high force population. These observations provide physical evidence for the existence of two binding sites in SERT. The dissociation rate constant of both binding sites was extracted by varying the dynamics of the force-probing experiments. Competition experiments revealed that the two sites are allosterically coupled and exert reciprocal modulation.